Processo sistemático para projeto, produção e adequação de mobiliário escolar que atenda aspectos ergonômicos e de qualidade - Pereira, Leandro Lopes (2007)
This work presents solutions in a systematic process for project, production and adequacy to the aspects of quality, ergonomic and of low cost. For this, four schools of the state net of education in the city of Santa Maria - RS. This research of field is of the quantitative-descriptive type, focusing the delineation and the analysis of the characteristics of the facts inquiry object. The used methods had been quantitative and of techniques as questionnaires and procedures of sampling for verification of hypotheses, description of population and the relations among variables. From the knowledge of the population, they had been defined, through calculations of sampling, the number of pupils, professors and directors to be searched through quantitative and qualitative questionnaires. The gotten results had allowed to a knowledge of the realities of the schools and its necessities. It was possible to analyze and to structuralize the involved aspects in the problem of the research, being allowed to consider adequate solutions. Of this form a flowchart for cycle of life of the joint pupil was elaborated who if composes in six elements: the project and production, distribution, schools, maintenance, deposit and disarrange, and recycling. In this direction, the concepts of reverse logistic had total application for solution of the problems related to the environment. Therefore this work besides presenting solutions can also provide an initiation to the awareness for the ambient problems serving as an applicable model to other areas.